Body, Violence, & Sexuality: Grotesque Aesthetics in Eka Kurniawan’s Novels - Rahmat Setiawan; Budiyono Sunu Catur; Nurhidayah Sri (English Letters Department, Faculty of Letters, Universitas Sanata Dharma, 2026)
This research examines how the aesthetics of the grotesque is represented in Eka Kurniawan’s novels. This research aims to re-read the discourse construction of these texts through the approaches of feminist body theory, trauma studies, and the concept of grotesque aesthetics. The type of this research is qualitative, with an approach of interpretative literary analysis within a deconstructive hermeneutic and critical cultural studies framework. The sources of the data are Kurniawan’s works: 1) Cantik Itu Luka (2015), 2) Lelaki Harimau (2004), and 3) Seperti Dendam, Rindu Harus Dibayar Tuntas (2014). The data are quotations [translated by the researcher] taken from the novels. The used data collection techniques are library study and documentation. The used technique of data analysis is thematic analysis within a deconstructive hermeneutic. The used data validity are semantic validity and expert judgement. The results reveal that grotesque aesthetics in Kurniawan’s novels are articulated through the representation of the body, violence, and sexuality as dynamic sites of resistance. The body emerges as a battlefield of power and resistance. Violation emerges trauma which operates as a collective and structural condition. Sexuality presents as a transgressive space deconstructing the normative gender and moral frameworks